Task-Specific Ionic Liquids as Extractants for the Solvent Extraction of Molybdenum(Vi) from Aqueous Solution Using Different Commercial Ionic Liquids as Diluents - Romero-Figueroa, J; Quijada-Maldonado, E (American Chemical Society, 2018)
In this work, the recovery of molybdenum(VI) (Mo) from aqueous solutions was carried out by solvent extraction (SX) using ammonium and phosphonium-based task-specific ionic liquids (TSILs) as extractants diluted in kerosene and two other hydrophobic room-temperature ionic liquids (RTILs). Four different TSILs were used as extractants: trioctylmethylammonium bis(2-ethylhexyl) phosphate [TOMA][D2EHP]; trioctylmethylammonium benzoate [TOMA][BA]; trihexyltetradecylphosphonium bis(2-ethylhexyl) phosphate [P6,6,6,14][D2EHP]; and trihexyltetradecylphosphonium benzoate [P6,6,6,14][BA]. These TSILs were synthesized to assess the effect of the cation and anion on the SX of Mo(VI). Experimental results indicated that high extraction percentages of Mo(VI) were obtained with all the synthesized TSILs. Besides that, the best cation was [TOMA]+ for all the diluents and [BA]- was the best anion when kerosene and 1-octyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [omim][Tf2N], were the diluents. Furthermore, the SX process using these ionic liquids followed an anion-exchange mechanism for kerosene and [omim][Tf2N] as diluents. Finally, the stripping was successfully performed with a solution of ammonium carbonate, and the extent of stripping depended on the selected diluent. © 2018 American Chemical Society.